Reimagining Culture and Arts Education through the Integration of Artificial Intelligence and the Sixth Industrial Revolution: Demands, Challenges, and Future Implications - Tabuena, Almighty Cortezo (Global Journal of Cultural Studies, 2025)
This scoping review explores the demands and integration of Artificial Intelligence (AI) and the Sixth Industrial Revolution (IR 6.0) in culture and arts education. It maps existing literature to understand how these technological advancements reshape educational practices, enhance creativity, and prepare learners for a rapidly evolving digital society. Anchored in Technological Determinism and Social Constructivism, the study investigates five key research questions on AI and IR 6.0 demands, integration challenges, alignment strategies, and educational implications. Findings highlight the transformative potential of AI in delivering personalized learning, fostering creativity, preserving cultural heritage, and facilitating immersive experiences through virtual and augmented reality. Likewise, IR 6.0 demands integration of digital tools, blended learning, interdisciplinary approaches, and sustainability. However, challenges such as resistance to change, limited expertise, unequal access to technology, and ethical concerns persist. The review underscores the need for proactive strategies including project-based learning, equitable access, ethical AI use, and continuous teacher training. It concludes that AI and IR 6.0, if harnessed responsibly, can enrich culture and arts education. Gaps in long-term impact studies, ethics, access, and student perceptions are identified, with recommendations for future research to foster inclusive, innovative, and future-ready educational practices.